Navigating Sustainable Fashion: The Impact of Social Media Marketing on Purchase Intention Through Brand Engagement and Brand Image in UNIQLO’s RE.UNIQLO Recycled Fashion in Indonesia - Veneranda Baby Viola Tio; Mustaruddin Mustaruddin; Ana Fitriana; Erna Listiana; Ahmadi Ahmadi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Effective marketing strategies are important to promote sustainable fashion due to increasing environmental awareness beyond Indonesians’ customers. This research using quantitative approach by structured questionnaire, non-probability sampling were used, which were purposive sampling, with the following criteria of who aged above 17 years old, Indonesian citizens, ever heard or saw about UNIQLO’s RE.UNIQLO program from UNIQLO’s social media platform (Instagram). This research is expecting to finds the effective strategies for UNIQLO and other industries that related by identified the effective Social Media Marketing strategies which could increase Brand Engagement and Brand Image to increase customers’ Purchase Intention on UNIQLO’s RE.UNIQLO recycled fashion products in Indonesia. This research found that Social Media Marketing significantly enhances Brand Engagement, Brand Image, and Purchase Intention, whereas Brand Engagement serving as a strong positive mediators, while Brand Image shows a negative effects due to the factors like price sensitivity and low awareness of sustainable fashion. Therefore, UNIQLO still should intensively advertising RE.UNIQLO recycled fashion across platforms, while stakeholders fund training and nationwide recycling campaigns. Lastly, further research ought to examine diverse variables in-terms of enhance the actual buyers on sustainable fashion products.